Optimizing Human Capital to Support Innovation and Organizational Agility in the Islamic Finance Industry - Lina Trisnawati; Gayuh Kawedar; Aina Izzati Zuhria; Agus Eko Sujianto; Amalia Nuril Hidayati (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
This study aims to analyze the role of human capital optimization in supporting innovation and organizational agility in the Islamic financial industry. The rapid development of the Islamic financial industry requires organizations to adapt to technological changes and evolving societal needs. In this context, human capital becomes a crucial factor, as the quality of human resources can influence an organization’s ability to create innovation and enhance competitiveness. This research employs a library research method with a qualitative approach. Data were collected from various sources, including books, scientific journals, articles, and previous studies relevant to the research topic. The data analysis technique was conducted descriptively and qualitatively through the processes of reading, reviewing, and interpreting literature related to human capital, innovation, organizational agility, and the Islamic financial industry. The findings indicate that human capital plays a significant role in encouraging innovation and improving organizational agility in the Islamic financial industry. The development of competencies, digital skills, and an adaptive work culture can help organizations face digital transformation and industry competition. Therefore, optimizing human capital is an important strategy to support the sustainability and competitiveness of the Islamic financial industry in the digital era.